Regeneración tisular guiada en periodoncia. Segunda parte. Acondicionadores radiculares - Gloria Nancy Arango-Hernández (Universidad de Antioquia, 1995)
The treatment of periodontal disease by traditional methods results in wound healing by the formation of a long junctional epithelium. The ultimate goal of periodontal therapy is to regenerate the periodontal supporting tissues lost to the inflamatory disease process. There has been a major effort to achive this goal by using either resorbable and nonresorbable physical barriers to impede epithelial migration or to treat diseased root surfaces with various agents: root conditioning solutions or growth factors. Recent investigations focusing on regeneration of the periodontium have attempted to define factor involved in the formation of a new connective tissue attachment to periodon-tally diseased or denuded root surfaces. After cell adhesion to substrate, one of thebiological events involved in tissue regeneration in specific cell directed migration or chemotaxis, wich is an essential feature biological processes in both health and disease. These cellular events are influenced and likely to be regulated by growth factors. In order to understand the regulatory role of growth factors in periodontal healing, it is important to charactireze the influences of involved growth factors on critical cellular events in the healing process. The more studied growth factor are: the beta transforming growth factor, platelet derived growth factor, insuline like growth factor and fibroblast growth factor. Tetracycline chorhidrate, citric acid, fibromectin and laminin are too important root conditioners.